Genistein Prevents Development of Spontaneous Ovarian Cancer and Inhibits Tumor Growth in Hen Model - Şahin, Kazım; Yenice, Engin; Bilir, Birdal; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Küçük, Ömer (Amer Assoc Cancer Research, 2019)
Genistein, the major isoflavone in soybean, has been reported to exert anticancer effects on various types of cancer including ovarian cancer; however, its chemopreventive effects and mechanisms of action in ovarian cancer have not been fully elucidated in spontaneously developing ovarian cancer models. In this study, we demonstrated the preventive effects and mechanisms of genistein in the laying hen model that develops spontaneous ovarian cancer at high incidence rates. Laying hens were randomized to three groups: control (3.01 mg/hen, n = 100), low (52.48 mg/hen n = 100), and high genistein supplementation (106.26 mg/hen/day; per group). At the end of 78 weeks, hens were euthanized and ovarian tumors were collected and analyzed. We observed that genis- tein supplementation significantly reduced the ovarian tumor incidence (P = 0.002), as well as the number and size of the tumors (P = 0.0001). Molecular analysis of the ovarian tumors revealed that genistein downregulated serum malondialdehyde, a marker for oxidative stress and the expression of NF kappa B and Bcl-2, whereas it upregulated Nrf2, HO-1, and Bax expression at protein level in ovarian tissues. Moreover, genistein intake decreased the activity of mTOR pathway as evidenced by reduced phosphorylation of p70S6K1, and 4E-BPI. Taken together, our findings strongly support the potential of genistein in the chemoprevention of ovarian cancer and highlight the effects of the genistein on the molecular pathways involved in ovarian tumorigenesis.
Keywords: Vegf Expression; Cell-Growth; Laying Hen; Risk; Nrf2; Soy; Pathway; Adenocarcinomas; Supplementation; Proliferation